Online Learning: Discipline and Responsibilities for Grade 3 Students Analysis: Analisis Karakter Disiplin dan Tanggung Jawab Pasca Pembelajaran Online pada Siswa Kelas 3 di Sekolah Dasar - Laili Zulfana; Akhtim Wahyuni (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to find out and analyze the disciplinary character and responsibility of students during offline learning. This study used a descriptive qualitative type. In this study, the data collection techniques used include observations, interviews, and documentation with the subject of 3 grade III students and 1 class III teacher. The results of this study show that after online learning students lack discipline in the aspect of arriving on time, abide by the rules or rules of the common/school. While in character responsibility students are lacking in terms of deeds and work on group assignments together. On the indicators of discipline students are good enough in doing or collecting assignments according to the specified time and follow the rules of good and correct language. Meanwhile, in the indicator of responsibility, students have carried out picketing well. Highlights: Offline learning and discipline: Highlighting the lack of discipline in arriving on time and following school rules after online learning. Responsibility and group work: Emphasizing students' deficiency in terms of deeds and working on group assignments together. Indicators of discipline and responsibility: Noting students' satisfactory performance in completing assignments on time and following rules of language, but also their successful picketing. Keywords: offline learning, disciplinary character, responsibility, qualitative study, data collection techniques